2021
DOI: 10.1007/s00348-020-03120-4
|View full text |Cite
|
Sign up to set email alerts
|

On the calibration of Astigmatism particle tracking velocimetry for suspensions of different volume fractions

Abstract: In the present study, we demonstrate for the first time how Astigmatism Particle Tracking Velocimetry (APTV) can be utilized to measure suspensions dynamics. Measurements were successfully performed in monodisperse, refractive index matched suspensions of up to a volume fraction of $$\varPhi =19.9\%$$ Φ = 19.9 % . For this, a small percentage ($$\varPhi <0.01\%$$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In Fig. 6c,d, we show a y plotted over a x which is required for the Euclidean calibration Brockmann et al 2020;Brockmann and Hussong 2021). Obviously here, for both the autocorrelation and the binarization approach, the curves for the small particles (small dots) and the large particles (large dots) intersect (Fig.…”
Section: Calibration Proceduresmentioning
confidence: 92%
See 3 more Smart Citations
“…In Fig. 6c,d, we show a y plotted over a x which is required for the Euclidean calibration Brockmann et al 2020;Brockmann and Hussong 2021). Obviously here, for both the autocorrelation and the binarization approach, the curves for the small particles (small dots) and the large particles (large dots) intersect (Fig.…”
Section: Calibration Proceduresmentioning
confidence: 92%
“…8a). Preliminary tests showed that a polynomial degree of at least 14 (as utilized here) is required to adapt to the different sets of calibration data that arise from different magnifications, particle sizes and processing parameters such as the autocorrelation coefficient (Brockmann and Hussong 2021). By plotting the fits of a y (denoted as a y ) over the fit of a x (denoted as a x ), the conventional Euclidean calibration (CEC) curve is obtained (Fig.…”
Section: Calibration Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Solely difficulties in handling of highly flammable or toxic liquids may restrict the choice of materials (Hassan and Dominguez-Ontiveros 2008;Wiederseiner et al 2011). Hence, this concept was already successfully applied for Particle Tracking Velocimetry (PTV) (Wang et al 2008), laser Doppler velocimetry (LDV) (Haam et al 2000), laser-induced fluorescence (LIF) (Chen et al 2005) and Astigmatism Particle Tracking Velocimetry (APTV) (Brockmann et al 2020;Brockmann and Hussong 2021) measurements in multiphase flows. An advantage of the PIV measurement technique compared to other optical, non-invasive measurement techniques like the APTV approach is that no sophisticated calibration technique is required and all suspension particles can be labelled and, therefore, contribute to the measurement result.…”
Section: Introductionmentioning
confidence: 99%